New design methods for large diameter piles under lateral loading for offshore wind applications - Byrne,BW; McAdam,R; Burd,HJ; Houlsby,GT; Martin,CM; Zdravkovi,L; Taborda,DMG; Potts,DM; Jardine,RJ; Sideri,M; Schroeder,FC; Gavin,K; et al. (2015)
Offshore wind turbines are typically founded on single large diameter piles, termed monopiles. Pile diameters of between 5mand 6mare routinely used, with diameters of up to 10 m, or more, being considered for future designs. There are concerns that current design approaches, such as the p − y method, which were developed for piles with a relatively large length to diameter ratio, may not be appropriate for large diameter monopiles. A joint industry project, PISA (PIle Soil Analysis), has been established to develop new design methods for large diameter monopiles under lateral loading. The project involves three strands of work; (i) numerical modelling; (ii) development of a new design method; (iii) field testing. This paper describes the framework on which the new design method is based. Analyses conducted using the new design method are compared with methods used in current practice.